Science Literacy in the Pre-primary and Early Stages of Primary Education as a Tool for Increasing an Interest in Science and Technical Studies - Janoušková, Svatava; Hubáčková, Lenka; Pumpr, Václav; Maršák, Jan (Scientia in educatione, 2020)
Science literacy – especially on the low- and upper- secondary education level – has been in the focus of educational professionals and scholars for a long time. In the last decade the number of studies dealing with the pre-primary and early primary science education increased. These studies explore the linkage between science education and the development of positive attitudes towards science education by children, and argue that if the attitudes are formed already in early childhood, they may have a significant influence on the child’s future – personal and professional – development. Based on the in-depth review of scientific literature the authors of this paper aim at providing the information about the key aspects considered necessary for the child’s science knowledge, skills, attitudes and values’ development. These aspects lay a foundation for the development of the Structure of the Science Literacy in Pre-Schools and Early Primary Schools. The Structure follows/complements the already existing Structure of the Science Literacy for the Lower Secondary Education Level in the Czech Republic. We hope the paper will contribute to the ongoing discussion about the prospects to increase an interest in science study as well as positive attitudes towards science education.